1992
DOI: 10.1007/bf00034957
|View full text |Cite
|
Sign up to set email alerts
|

Microprojectile bombardment of plant tissues increases transformation frequency by Agrobacterium tumefaciens

Abstract: Bombardment of plant tissues with microprojectiles in an effective method of wounding to promote Agrobacterium-mediated transformation. Tobacco cv. Xanthi leaves and sunflower apical meristems were wounded by microprojectile bombardment prior to application of Agrobacterium tumefaciens strains containing genes within the T-DNA encoding GUS or NPTII. Stable kanamycin-resistant tobacco transformants were obtained using an NPTII construct from particle/plasmid, particle-wounded/Agrobacterium-treated or scalpel-wo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
67
0
7

Year Published

1995
1995
2013
2013

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 162 publications
(76 citation statements)
references
References 37 publications
2
67
0
7
Order By: Relevance
“…In tobacco, leaves were wounded by microprojectile prior to inoculate with Agrobacterium strain LBA4404 containing nptII gene, and transferred to regeneration medium with 100 mg/l kanamycin for selection (Bidney et al, 1992). High frequency of transformation, based on kanamycin resistance in selection medium containing 100 mg/l kanamycin was obtained from lettuce cotyledon explants co-cultivated with A. tumefaciens vectors (Torres et al, 1993).…”
Section: Kanamycin Selectionmentioning
confidence: 99%
“…In tobacco, leaves were wounded by microprojectile prior to inoculate with Agrobacterium strain LBA4404 containing nptII gene, and transferred to regeneration medium with 100 mg/l kanamycin for selection (Bidney et al, 1992). High frequency of transformation, based on kanamycin resistance in selection medium containing 100 mg/l kanamycin was obtained from lettuce cotyledon explants co-cultivated with A. tumefaciens vectors (Torres et al, 1993).…”
Section: Kanamycin Selectionmentioning
confidence: 99%
“…To overcome this barrier of regeneration, particle bombardment method has been used to transform recalcitrant crops (Christou,1992;John and Keller, 1996;McCabe et al, 1988;McCabe and Martinell, 1993). Recently it has been shown that particle bombardment of plant tissues enhances the transformation efficiency through Agrobacterium (Bidney et al, 1992;Finer and McMullen,1990).…”
Section: Introductionmentioning
confidence: 99%
“…To promote the reactivation of cell metabolism, phytohormones, as used by Bidney et al (1992) for enlargement of sunflower menstems, were applied for 24 h prior to bombardment. These hormones are known to enhance the mitotic activity of (Jegla and Sussex, 1989), an increase in mitotic activity of those cells might even promote the recovery of chimeras with transgenic offspring.…”
Section: Resultsmentioning
confidence: 99%